Genomic homogeneity between Mycobacterium avium subsp. avium and Mycobacterium avium subsp. paratuberculosis belies their divergent growth rates - Li Ling-Ling; Zhang Qing; Bannantine John P; Kapur Vivek (BMC Microbiology, 2003)
Abstract Background Mycobacterium avium subspecies avium (M. avium) is frequently encountered in the environment, but also causes infections in animals and immunocompromised patients. In contrast, Mycobacterium avium subspecies paratuberculosis (M. paratuberculosis) is a slow-growing organism that is the causative agent of Johne's disease in cattle and chronic granulomatous infections in a variety of other ruminant hosts. Yet we show that despite their divergent phenotypes and the diseases they present, the genomes of M. avium and M. paratuberculosis share greater than 97% nucleotide identity over large (25 kb) genomic regions analyzed in this study. Results To characterize genome similarity between these two subspecies as well as attempt to understand their different growth rates, we designed oligonucleotide primers from M. avium sequence to amplify 15 minimally overlapping fragments of M. paratuberculosis genomic DNA encompassing the chromosomal origin of replication. These strategies resulted in the successful amplification and sequencing of a contiguous 11-kb fragment containing the putative Mycobacterium paratuberculosis origin of replication (oriC). This fragment contained 11 predicted open reading frames that showed a conserved gene order in the oriC locus when compared with several other Gram-positive bacteria. In addition, a GC skew analysis identified the origin of chromosomal replication which lies between the genes dnaA and dnaN. The presence of multiple DnaA boxes and the ATP-binding site in dnaA were also found in M. paratuberculosis. The strong nucleotide identity of M. avium and M. paratuberculosis in the region surrounding the origin of chromosomal replication led us to compare other areas of these genomes. A DNA homology matrix of 2 million nucleotides from each genome revealed strong synteny with only a few sequences present in one genome but absent in the other. Finally, the 16s rRNA gene from these two subspecies is 100% identical. Conclusions We present for the first time, a description of the oriC region in M. paratuberculosis. In addition, genomic comparisons between these two mycobacterial subspecies suggest that differences in the oriC region may not be significant enough to account for the diverse bacterial replication rates. Finally, the few genetic differences present outside the origin of chromosomal replication in each genome may be responsible for the diverse growth rates or phenotypes observed between the avium and paratuberculosis subspecies.